What factors influence the lifetime of pull requests?. (21st December 2020) - Moreira Soares, Daricélio; de Lima Júnior, Manoel Limeira; Murta, Leonardo; Plastino, Alexandre
Summary: When external contributors want to collaborate with an open‐source project, they fork the repository, make changes, and send a pull request to the core team. However, the lifetime of a pull request, defined by the time interval between its opening and its closing, has a high variation, potentially affecting the contributor engagement. In this context, understanding the root causes of pull request lifetime is important to both the external contributors and the core team. The former can adopt strategies that increase the chances of fast review, while the latter can establish priorities in the reviewing process, alleviating the pending tasks and improving the software quality. In this work, we mined association rules from 97, 463 pull requests from 30 projects in order to find characteristics that have affected the pull requests lifetime. In addition, we present a qualitative analysis, helping to understand the patterns discovered from the association rules. The results indicate that: (i) contributions with shorter lifetimes tend to be accepted; (ii) structural characteristics, such as number of commits, changed files, and lines of code, have influence, in an isolated or combined way, on the pull request lifetime; (iii) the files changed and the directories to which they belong can be robust predictors for pull request lifetime; (iv) the profile of external contributors and their social relationships have influence on lifetime; and (v) the number of comments in a pull request, as well as the developer responsible for the review, are important predictors for its lifetime.